Beyond the Border : The German-Jewish Legacy Abroad - Aschheim, Steven E., 1942- (Book collections on Project MUSE., 2018)
The modern German-Jewish experience through the rise of Nazism in 1933 was characterized by an explosion of cultural and intellectual creativity. Yet well after that history has ended, the influence of Weimar German-Jewish intellectuals has become ever greater. Hannah Arendt, Gershom Scholem, Theodor Adorno, Walter Benjamin, Franz Rosenzweig, and Leo Strauss have become household names and possess a continuing resonance. Beyond the Border seeks to explain this phenomenon and analyze how the German-Jewish legacy has continuingly permeated wider modes of Western thought and sensibility, and why these emigres occupy an increasingly iconic place in contemporary society. Steven Aschheim traces the odyssey of a fascinating group of German-speaking Zionists--among them Martin Buber and Hans Kohn--who recognized the moral dilemmas of Jewish settlement in pre-Israel Palestine and sought a binationalist solution to the Arab-Israel conflict. He explores how German-Jewish emigre historians like Fritz Stern and George Mosse created a new kind of cultural history written against the background of their exile from Nazi Germany and in implicit tension with postwar German social historians. And finally, he examines the reasons behind the remarkable contemporary canonization of these Weimar intellectuals--from Arendt to Strauss--within Western academic and cultural life. Beyond the Border is about more than the physical act of departure. It also points to the pioneering ways these emigres questioned normative cognitive boundaries and have continued to play a vital role in addressing the predicaments that engage and perplex us today.